2022
DOI: 10.1111/ecpo.12212
|View full text |Cite
|
Sign up to set email alerts
|

The effect of presidential election outcomes on alcohol drinking

Abstract: The growing political polarization and the increasing use of social media have been linked to straining social ties worldwide. The 2016 presidential elections in the United States reflected this trend with reports of fear and anxiety among voters. We examine how election results can be linked to episodes of anxiety through the use of alcohol as self‐medication. We analyze a daily dataset of household purchases of alcohol in the weeks following presidential elections. We find that, within 30 days from Election … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The increase in anger and distress reported by Labour party supporters in response to Johnson’s reward smiles is consistent with findings from the psychological literature on losing [ 45 ]. Previous work has shown that the supporters of the election loser show a decrease in various measures of wellbeing and even a rise in mental health issues and unhealthy behaviours following the election loss [ 46 , 47 ]. Indeed, such an effect was revealed across 25 European countries and was also driven by a clear partisan affiliation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in anger and distress reported by Labour party supporters in response to Johnson’s reward smiles is consistent with findings from the psychological literature on losing [ 45 ]. Previous work has shown that the supporters of the election loser show a decrease in various measures of wellbeing and even a rise in mental health issues and unhealthy behaviours following the election loss [ 46 , 47 ]. Indeed, such an effect was revealed across 25 European countries and was also driven by a clear partisan affiliation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is deeply concerning, considering that the standard prevalence rate of PTSD in any given year is about 3.5% (Kessler, Chiu et al, 2005). While past studies have linked election outcomes to negative health outcomes like depression (Yan et al, 2021), anxiety (Nayak et al,, 2021), sleep issues (Nayak et al 2021), drinking (Musse & Schneider, 2023), smoking (Samson, 2015), and stress (Smith, 2022; Smith et al, 2019), this is the first study to the authors’ knowledge to find measurable levels of post-traumatic stress potentially linked to an election.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 2016 election, scholars have linked growing divisions within American communities to changes in several health indicators. For example, politically isolated residents report more days of poor physical health (Fraser et al, 2022; Nayak et al, 2021; Panagopoulos et al, 2021) and poor mental health (Yan et al, 2021), including increased incidence of depression (Yan et al, 2021), anxiety (Hackett et al, 2018; Nayak et al, 2021), stress (APA, 2017), sleep issues (Nayak et al, 2021), and drinking (Musse & Schneider, 2023). A national survey conducted in 2017 revealed that 11.5% of Americans believed that politics had adversely affected their physical health, with 40% reporting higher stress due to politics, 20% reporting lost sleep, and 20% reporting lost friendships due to their political views (Smith et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure to stressful and isolating events can increase the risk of premature mortality through biological mechanisms such as elevated cortisol ( Stanton et al, 2010 ; Waismel-Manor et al, 2011 ), and behavioral mechanisms, such as increases in disordered tobacco, alcohol, and drug use ( Musse & Schneider, 2022 ). Long-term exposure to psychosocial stressors including feelings of anger and hostility, experiencing anxiety, social conflict, and feelings of non-specific stress are associated with increased cardiovascular disease burden ( Everson-Rose & Lewis, 2005 ).…”
Section: Introductionmentioning
confidence: 99%